1993
DOI: 10.1126/science.8456285
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative proliferation in inner ear sensory epithelia from adult guinea pigs and humans

Abstract: Supporting cells in the vestibular sensory epithelia from the ears of mature guinea pigs and adult humans proliferate in vitro after treatments with aminoglycoside antibiotics that cause sensory hair cells to die. After 4 weeks in culture, the epithelia contained new cells with some characteristics of immature hair cells. These findings are in contrast to expectations based on previous studies, which had suggested that hair cell loss is irreversible in mammals. The loss of hair cells is responsible for hearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
334
0
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(350 citation statements)
references
References 9 publications
11
334
0
5
Order By: Relevance
“…Perhaps the most notable difference between hair cells of the utricle and those of the mammalian organ of Corti is that the vestibular system has some capacity to regenerate hair cells Warchol et al, 1993). Despite these differences, vestibular hair cells have proven useful in tracking the cellular mechanisms underlying ototoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most notable difference between hair cells of the utricle and those of the mammalian organ of Corti is that the vestibular system has some capacity to regenerate hair cells Warchol et al, 1993). Despite these differences, vestibular hair cells have proven useful in tracking the cellular mechanisms underlying ototoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Progressive hearing loss is common and most forms of deafness are irreversible. A low level of regeneration has been observed in mammalian vestibular epithelia Warchol et al 1993), for which attempts to establish cell lines have already been made Zheng et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Assembling evidences support the hypothesis that Atoh1 is the determinant factor that drive stem cell differentiation and development. All the auditory and vestibular hair cells were absent in Atoh1 deficient mice, 2 4 and ectopic re-introduction of wild-type Atoh1 restored the hair cell fate within both the pro-sensory domain and non-sensory regions of the cochlea. 25 In line with these observations, our data demonstrated that Celastrol enhanced neuronal-like cell identity in the inner ear stem cell population as well as their electrophysiological function, which was highly likely to be mediated by the up-regulation of Atoh1.…”
Section: Discussionmentioning
confidence: 92%
“…Although the modest regenerative capacity has been observed in rodent vestibular sensory epithelia, 4 no hair cell regeneration occurred in adult mammalian cochlea at all. The endeavor to activate the regenerative capacity for medical purpose has been disappointing so far, which partially attributes to highly differentiated and specified cells in the delicate architecture of human auditory system.…”
Section: Introductionmentioning
confidence: 95%